The dynamics of quantitative SARS‐CoV‐2 antispike IgG response to BNT162b2 vaccination. Issue 12 (5th August 2021) - Kaneko, Shun; Kurosaki, Masayuki; Sugiyama, Toru; Takahashi, Yuka; Yamaguchi, Yoshimi; Nagasawa, Masayuki; Izumi, Namiki
Abstract: Vaccination for SARS‐CoV‐2 is necessary to overcome coronavirus disease 2019 (COVID‐19). However, the time‐dependent vaccine‐induced immune response is not well understood. This study aimed to investigate the dynamics of SARS‐CoV‐2 antispike immunoglobulin G (IgG) response. Medical staff participants who received two sequential doses of the BNT162b2 vaccination on days 0 and 21 were recruited prospectively from the Musashino Red Cross Hospital between March and May 2021. The quantitative antispike receptor‐binding domain (RBD) IgG antibody responses were measured using the Abbott SARS‐CoV‐2 IgGII Quant assay (cut off ≥50 AU/ml). A total of 59 participants without past COVID‐19 history were continuously tracked with serum samples. The median age was 41 (22–75) years, and 14 participants were male (23.7%). The median antispike RBD IgG and seropositivity rates were 0 (0–31.1) AU/ml, 0.3 (0–39.5) AU/ml, 529.1 (48.3–8711.4) AU/ml, 18, 836.9 (742.2–57, 260.4) AU/ml, and 0%, 0%, 98.3%, and 100% on days 0, 3, 14, and 28 after the first vaccination, respectively. The antispike RBD IgG levels were significantly increased after day 14 from vaccination ( p  < 0.001) The BNT162b2 vaccination led almost all participants to obtain serum antispike RBD IgG 14 days after the first dose. Highlights: Highlights The quantitative SARS‐Cov‐2 anti‐spike receptor‐binding domain (RBD) IgG antibody responses were measured in the 59 medical staff participants who received two sequential doses (day 0, 21) of the BNT162b2 vaccination. The quantitative anti‐spike RBD IgG antibody responses were measured using the Abbott SARS‐CoV‐2 IgGⅡ Quant assay (cut off ≥50 AU/mL). The median anti‐spike RBD IgG and seropositivity rates were 0 (0–31.1) AU/mL, 0.3 (0–39.5) AU/mL, 529.1 (48.3–8711.4) AU/mL, 18836.9 (742.2–57260.4) AU/mL, and 0%, 0%, 98.3%, and 100% on days 0, 3, 14, and 28 after the first vaccination, respectively.